Relationship Between Educational Level and Maternal Age on The Nutritional Status Stunted Children - Essa Andaru Anugraheni; Siti Arifah (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2024)
The nutritional status of children, especially in infancy, is an important aspect in health development and growth. Factors such as education level and maternal age are thought to have an influence on children's nutritional status. This study aims to analyze the relationship between education level and maternal age with infant nutritional status at the Sawit 1 Health Center, Boyolali Regency. This study used a correlational method with a cross-sectional approach. The study was conducted at the Sawit 1 Health Center, Boyolali Regency, which was implemented in September 2024. The population in the study were all mothers who had children aged 6 months to 1 year at the Sawit 1 Health Center, Boyolali Regency. The study sample consisted of 25 mothers who had babies aged 6-12 months. Measurement of nutritional status was carried out by measuring the length and weight of the baby, while maternal demographic data were obtained through a questionnaire. Data analysis used the Pearson correlation test to see the relationship between variables. The results of the study showed that there was no significant relationship between the level of maternal education and the nutritional status of infants (r = 0.051; p-value = 0.807), and there was no significant relationship between the age of the mother and the nutritional status of infants (r = -0.082; p-value = 0.696). Thus, this study concluded that the level of education and age of the mother did not have a significant relationship with the nutritional status of infants in the study area. It is necessary to improve nutritional education programs for mothers, strengthen the role of health cadres, and community-based counseling to increase awareness of the importance of nutrition for infants. Keywords: Education, Age, Nutritional Status, Children, Stunting